Bringing computing into the Middle Ages: the making of sybils!, a multimedia CD-ROM. - Garay, C; Walker, D (Literary & Linguistic Computing, 2000)
Kathleen Garay teaches in the Department of History and Women's Studies at McMaster University, where she is also an archivist. David Walker is the Project Manager of multimedia instructional computing at McMaster University. With the assistance of a small group of medievalists and a programmer-graphic designer they created a multimedia CD-ROM-based program on Women in the Middle Ages and Renaissance. The CD-ROM was used in class for the first time in the 1996-7 academic year, and a revised version is currently being distributed by an academic multimedia publisher. This paper presents a synthesis of two perspectives on the development of this teaching resource: teacher and computing professional.